Rotación de jaragua y estrella con vaquillas de leche en crecimiento - Alvarado, M.=700 1 La Hoz, E.; Figueroa, N.
Sumario (Es)
Keywords: HYPARRHENIA RUFA; ROTACION DE CULTIVOS; VACAS LECHERAS; CRECIMIENTO